In vivo monitoring of the TR4 anti-Notch fusion protein: an imaging approach. - Epenetos, Agamemnon Anthony; Prokopi, Marianna; Pitsillides, Costas; Kousparou, Christina; Filipovic, Aleksandra; Anayiotos, Andreas; Kapnisis, Konstantinos; Deonarain, Mahendra (My University, 2016)
Background: The Notch pathway has been associated with cancer and is implicated in tumorigenesis and regulation of cell fate. This pathway is an attractive target for the development of novel anti-Notch cancer therapeutics. We have generated a novel fusion protein TR4 that inhibits Notch at transcriptional level and can reduce tumor growth Methods: TR4 consists of the truncated Mastermind (MAML) peptide that inhibits Notch and the cell penetrating peptide Antennapedia (Antp). We have investigated the pharmacokinetic and pharmacodynamic behavior of fluorescent TR4 using pharmacokinetics and toxicology together with innovative in vivoflow cytometry and whole body fluorescence reflectance imaging Results: The TR4 fusion protein was conjugated to fluorescent markers to enable detection via fluorescence based in vitro and in vivo imaging systems. The cell membrane translocation ability of the TR4 conjugate was confirmed in vitro and in vivo for toxicity at escalating dosages in immune-competent mice . It did not induce any overt toxicity or organ dysfunction . Following IV administration animals were imaged with the in vivo flow cytometer; free/non-internalized protein was rapidly cleared from circulation, fluorescent TR4 appeared to collect in some of the major organs/tissues imaged and was cleared within 24 hrs via the gastrointestinal tract. In vivoimaging demonstrated a reduction in tumor growth over time in the treated mice as compared to controls. Conclusions: The TR4 fusion protein is able to translocate into the cell nucleus and suppress Notch activation reverting the transformed phenotype and inducing apoptosis in highly metastatic epithelial human breast cancer. Furthermore,the studies investigated the dynamics , mode of action and helped optimize the TR4 peptide as a novel therapy for cancer and cancer stem cells..
Keywords: Tumorigenesis; Anti-Notch cancer therapeutics